The Development of E-Modules in the Curriculum and Learning Course Using the Kvisoft Flipbook Maker Application - Rahmi, Cici Utia; Eldarni, Eldarni; Anugerah, Septriyan; Pratiwi, Rahmi (The Future of Education Journal, 2025)
The problem found in the field is that in learning, the media used are less varied and tend to be monotonous in the form of print media. This causes a lack of enthusiasm among students in understanding the material and completing tasks. Therefore, an E-module is developed to support learning. This study aims to develop and implement features in the E-module to assist students in exploring their ideas and gaining new knowledge. Several features developed include learning materials and learning videos. Testing was conducted on a group of students by observing their level of engagement and responses to the available features. This study uses a Research and Development approach with the 4D development model. Research and Development is a research method used to produce a specific product and test the practicality of the product. The 4-D development model consists of define, design, development, and dissemination. During the development phase, a validation test was conducted by three validators: two media experts and one material expert. A practical test was conducted with students from the Faculty of Education in the course of Curriculum and Learning to test the practicality of the developed E-module. The assessment results from the material validator showed an average score of 99%, categorized as "very valid." The media expert validation results from Validator I showed an average score of 99%, categorized as "very valid," while the validation results from Validator II showed an average score of 93%, categorized as "very valid." The E-module can be considered practical because it underwent a practical test with an average score of 82%. Based on the results of the validity and practicality tests, it can be concluded that this E-module is feasible to be implemented.